WRKY1 represses the WHIRLY1 transcription factor to positively regulate plant defense against geminivirus infection - Sun, Shaoshuang; Li, Shupeng; Zhou, Xueping; Yang, Xiuling (PLoS pathogens, 2023)
Geminiviruses constitute the largest group of known plant viruses and cause devastating diseases and economic losses in many crops worldwide. Due to limited naturally occurring resistance genes, understanding plant antiviral defense against geminiviruses is critical for finding host factors of geminiviruses and development of strategies for geminivirus control. Here we identified NbWRKY1 as a positive regulator of plant defense against geminivirus infection. Using tomato yellow leaf curl China virus/tomato yellow leaf curl China betasatellite (TYLCCNV/TYLCCNB) as a representative geminivirus, we found that NbWRKY1 was upregulated in response to TYLCCNV/TYLCCNB infection. Overexpression of NbWRKY1 attenuated TYLCCNV/TYLCCNB infection, whereas knockdown of NbWRKY1 enhanced plant susceptibility to TYLCCNV/TYLCCNB. We further revealed that NbWRKY1 bound to the promoter of the NbWHIRLY1 (NbWhy1) transcription factor and inhibited the transcription of NbWhy1. Consistently, NbWhy1 negatively regulates plant response against TYLCCNV/TYLCCNB. Overexpression of NbWhy1 significantly accelerated TYLCCNV/TYLCCNB infection. Conversely, knockdown of NbWhy1 led to impaired geminivirus infection. Furthermore, we demonstrated that NbWhy1 interfered with the antiviral RNAi defense and disrupted the interaction between calmodulin 3 and calmodulin-binding transcription activator-3. Moreover, the NbWRKY1-NbWhy1 also confers plant antiviral response toward tomato yellow leaf curl virus infection. Taken together, our findings suggest that NbWRKY1 positively regulates plant defense to geminivirus infection by repressing NbWhy1. We propose that the NbWRKY1-NbWhy1 cascade could be further employed to control geminiviruses.